Predictive role of serum sST2 for heart failure in children with severe pneumonia - Qingsong Wu; Xinxin Zheng; Xinfan Lin; Linfeng Xie; Liangwan Chen; Zhihuang Qiu (European Journal of Medical Research)
Abstract Objective To evaluate the predictive value of soluble suppression of tumorigenesis-2 (sST2) for heart failure (HF) in children hospitalized with severe pneumonia. Methods A total of 109 children with severe pneumonia who were admitted to our hospital between January 2022 and December 2023 were selected. They were divided into HF and non-HF groups based on whether they developed HF. Clinical characteristics and clinical outcome data of the two groups were analyzed using relative factors analysis and logistic regression analysis. Results The HF and non-HF groups consisted of 35 and 74 patients, respectively. Significant differences were observed between the groups in terms of age [20.0 (11.0–38.0) vs. 60.0 (36.0–96.0) months, P < 0.001], body mass index (16.7 ± 2.0 vs. 18.3 ± 2.5 kg/m2, P < 0.001), and body surface area (0.52 ± 0.13 vs. 0.75 ± 0.23 m2, P < 0.001), with all values being lower in the HF group as compared to the non-HF group. Serum levels of sST2 (7.01 ± 2.31 vs. 4.38 ± 1.65 ng/mL, P < 0.001) and NT-proBNP [86.0 (78.5–108.5) vs. 65.0 (25.0–83.0) pg/mL, P < 0.001] were significantly higher in the HF group. The incidence of type I respiratory failure was also significantly higher in the HF group as compared to the non-HF group (45.7% vs. 25.7%, P = 0.005). Univariate logistic regression analysis revealed that age, body surface area, body mass index, type I respiratory failure, C-reactive protein level, NT-proBNP level, and sST2 level were significant risk factors for HF in children with severe pneumonia. Multivariate analysis identified sST2 levels > 5.84 ng/mL as an independent risk factor for HF [odds ratio (OR) = 3.974, 95% confidence interval (CI) 1.266–12.323, P = 0.003], with an area under the curve (AUC) of 0.828 (95% CI 0.718–0.927), sensitivity of 89.3%, and specificity of 78.8%. Conclusion Elevated sST2 shows potential as an independent risk factor for HF in children with severe pneumonia, but further studies are needed before routine clinical adoption.